A Case Report: Insulin-Induced Edema in a 13-Year-Old Girl - Abdulmoein E. Al-Agha; Ali H. Ocheltree (Journal of King Abdulaziz University: Medical Sciences, 2023)
A 13-year-old girl with type one diabetes mellitus poorly controlled for seven years, presented with total body edema and rapid weight gain (7 kg in 10 days). The edema developed one week after the initiation of an intensive insulin treatment. Initially, it started as lower limb edema; other causes of edema were excluded. With current trends toward intensive insulin therapy, clinicians need to be aware of the existence of Insulin Edema Syndrome. Its occurrence needs be documented and differentiated from other causes of edema.